Multilayer inductor and method for manufacturing the same
By using an amorphous mixture of silicon oxide and carbon as the coupling part in the magneton layer, the problem of insufficient mechanical strength caused by the polymerization of magnetic particles after high-temperature heat treatment in the prior art is solved, and the dual improvement of mechanical strength and insulation reliability is achieved.
Patent Information
- Application Number
- JP2024020319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-14
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-02-18
AI Technical Summary
The prior art has challenges in improving the mechanical strength and insulation reliability of the magnetic particle layer of metal magnetic particle, especially in high-temperature heat treatment, magnetic particles are prone to polymerization, resulting in insufficient mechanical strength.
An amorphous mixture containing silicon oxide and carbon is used as a coupling portion connecting a plurality of metal magnetic particles, the molar ratio of silicon of the coupling portion is 1 and the molar ratio of carbon is 0.4 or higher.
By this method, it is possible to ensure the reliability of insulation while improving the mechanical strength of the magneton layer and avoid the polymerization of magnetic particles caused by high-temperature heat treatment.
Smart Images

Figure 0007665815000002 
Figure 0007665815000003 
Figure 0007665815000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated inductor and a method for manufacturing a laminated inductor. [Background technology]
[0002] Coil components using metal magnetic particles with excellent DC bias characteristics instead of ferrite have been proposed. Metal magnetic particles have low insulating properties, so it is known that the surfaces of the metal magnetic particles are coated with an insulating film such as a silicon oxide film or an aluminum oxide film. For example, a magnetic base is known that has metal magnetic particles coated with an insulating film and a glass component containing silicon, boron, and an alkali metal (e.g., Patent Document 1). Also, a magnetic base is known that has metal magnetic particles coated with an insulating film and a silicone resin (e.g., Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2014 / 024976 [Patent Document 2] JP 2019-153614 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to improve the reliability of coil components, it is desirable for the magnetic base to have high insulation reliability and mechanical strength. In addition, for example, in order to increase the filling rate of metal magnetic particles and improve magnetic properties, it is conceivable to form a magnetic base by bonding the oxide films of a plurality of metal magnetic particles whose surfaces are covered with oxide films. In this case, heat treatment at high temperatures is required to bond the oxide films of the metal magnetic particles. For example, Patent Document 2 performs heat treatment at high temperatures. However, when heat treatment is performed at high temperatures, the metal magnetic particles bond (neck) with each other beyond the oxide. Therefore, it is difficult to perform heat treatment at high temperatures in order to prevent the metal magnetic particles from sintering, and as a result, it is difficult to obtain a magnetic base with high mechanical strength.
[0005] The present invention has been made in consideration of the above problems, and has an object to improve mechanical strength while ensuring insulation reliability. [Means for solving the problem]
[0006] The present invention relates to a method for producing a magnetic material comprising: and before A bonding portion that bonds the plurality of metal magnetic particles; a magnetic base in which a plurality of magnetic layers each including: The coupling portion is The main component is silicon oxide, Carbon and 、 It is an amorphous mixture containing a molar ratio, which is a ratio of a molar amount of carbon contained in the bonding portion to a molar amount of silicon contained in the bonding portion taken as 1, being 0.4 or more; It is.
[0007] In the above configuration, the silicon contained in the bonding portion Molar amount of The molar ratio, which is the ratio of the molar amount of carbon contained in the bond, to the molar amount of carbon contained in the bond is set to 1, and the molar ratio can be 5 or less.
[0008] The present invention provides a magnetic substrate comprising a plurality of magnetic layers laminated together, each of which includes a plurality of metal magnetic particles and a bonding portion bonding the plurality of metal magnetic particles together; a coil conductor formed by a conductor pattern provided on the plurality of magnetic layers and embedded in the magnetic substrate; and an external electrode provided on a surface of the magnetic substrate and connected to the coil conductor, the bonding portion being an amorphous mixture containing an oxide of silicon as a main component and carbon, and containing an oxide of at least one element selected from the group consisting of aluminum, chromium, magnesium, titanium, and zirconium; The molar ratio, which is the ratio of the molar amount of carbon contained in the bonding portion to the total molar amount of silicon, aluminum, chromium, magnesium, titanium, and zirconium contained in the bonding portion taken as 1, is 0.4 or more. , which is a multilayer inductor .
[0009] In the above configuration, the molar ratio, which is the ratio of the molar amount of carbon contained in the bonding portion to the total molar amount of silicon, aluminum, chromium, magnesium, titanium, and zirconium contained in the bonding portion, can be 5 or less. In the above configuration, the metal magnetic particles may be provided with an oxide film that covers at least a portion of the surface of the metal magnetic particles and contains substantially no carbon therein, and the bonding portion may be configured to bond the metal magnetic particles together by bonding the oxide films together via the bonding portion.
[0011] In the above configuration, the plurality of metal magnetic particles may be composed mainly of iron. In the above-mentioned configuration, the magnetic substrate may have a region where carbon is present other than the bonded portion. In the above configuration, the region where carbon is present other than the bond portion may be a triple point portion surrounded by three or more of the plurality of metal magnetic particles. In the above configuration, the conductor pattern may include silver, palladium, copper, or aluminum.
[0012] The present invention relates to a step of preparing a magnetic paste by mixing the magnetic particles, a resin composition containing a binder resin and a resinate containing silicon, and a solvent; a step of forming a magnetic layer using the magnetic paste; a step of forming a conductor pattern on the magnetic layers; a step of laminating the magnetic layers on which the conductor patterns are formed, and then heat-treating the magnetic layers to form bonding parts on surfaces of the magnetic particles, the bonding parts being an amorphous mixture containing an oxide of silicon contained in the resinate as a main component and containing carbon, thereby forming a magnetic base in which the magnetic particles are bonded to each other via the bonding parts and which incorporates a coil conductor formed by the conductor patterns; and a step of forming an external electrode connected to the coil conductor on a surface of the magnetic base, wherein a molar ratio, which is a ratio of a molar amount of carbon contained in the bonding parts to a molar amount of silicon contained in the bonding parts, is 0.4 or more. It is.
[0013] In the above configuration, in the process of forming the magnetic base, the plurality of magnetic layers can be heat-treated to thermally decompose the binder resin prior to the resinate, and then the silicon component of the resinate is made amorphous while incorporating carbon contained in the resinate, thereby forming the bonding portion on the surface of the plurality of metal magnetic particles. In the above configuration, in the step of preparing the plurality of metal magnetic particles, the plurality of metal magnetic particles having an oxide film on their surfaces are prepared, and in the step of forming the magnetic base, the magnetic base is formed in which the oxide film of each of the plurality of metal magnetic particles is bonded via the bonding portion. Effect of the Invention
[0014] According to the present invention, it is possible to improve the mechanical strength while ensuring the insulation reliability. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a cross-sectional view showing a magnetic substrate according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a magnetic substrate according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a perspective view showing a coil component according to a third embodiment of the present invention. [Figure 4] FIG. 4 is an exploded perspective view showing a coil component according to a third embodiment of the present invention. [Diagram 5] FIG. 5 is a side view showing a coil component according to a fourth embodiment of the present invention. [Figure 6] FIG. 6 is a perspective view showing an electronic device according to a fifth embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as appropriate. However, the present invention is not limited to the illustrated embodiment. In addition, components common to multiple drawings are given the same reference numerals throughout the multiple drawings. Please note that the drawings are not necessarily drawn to scale for the sake of convenience.
[0017] [First embodiment] Fig. 1 is a cross-sectional view showing a magnetic substrate according to a first embodiment of the present invention. Fig. 1 shows an enlarged view of a portion of the magnetic substrate 100 according to the first embodiment. Referring to Fig. 1, a plurality of metal magnetic particles 10 are bonded via insulating bonding parts 11 to form the insulating magnetic substrate 100. The presence of the bonding parts 11 can be recognized as a difference in contrast (brightness) in an image of the cross section of the magnetic substrate 100 photographed at about 5000 times magnification by a scanning electron microscope (SEM), for example.
[0018] The metal magnetic particles 10 are soft magnetic particles mainly composed of iron, and may be alloy particles or pure iron particles. The metal magnetic particles 10 mainly composed of iron means that the ratio of iron to the total amount of elements constituting the metal magnetic particles 10 is 50 wt% (weight percent) or more, 80 wt% or more, 90 wt% or more, or 95 wt% or more. For example, when the metal magnetic particles 10 are pure iron particles, the ratio of iron may be 98 wt% or more, and the remainder may be impurities or the like. For example, the metal magnetic particles 10 may be alloy particles containing iron and silicon, or alloy particles containing iron and one or more metal elements M having a higher ionization tendency than iron (easier to oxidize than iron). Examples of the metal elements M include chromium (Cr), aluminum (Al), zirconium (Zr), titanium (Ti), and manganese (Mn). As an example, the metal magnetic particle 10 may be an alloy particle of iron, silicon, and one or more metal elements M (e.g., at least one of chromium and aluminum) having a higher ionization tendency than iron. The percentage of iron may be 93 wt% to 98 wt%, the percentage of silicon may be 1.5 wt% to 6.5 wt%, and the percentage of the metal element M may be 0.5 wt% to 5.5 wt%. The metal magnetic particle 10 may contain unintended impurities such as oxygen and / or carbon. The percentage of the impurities may be 2 wt% or less. The metal magnetic particle 10 may also contain cobalt (Co), nickel (Ni), copper (Cu), sulfur (S), phosphorus (P), and / or boron (B), etc. The composition ratio of the metal magnetic particle 10 can be calculated, for example, by taking an image of a cross section of the magnetic substrate 100 with a scanning electron microscope at about 3000 to 20000 times magnification and performing ZAF analysis using energy dispersive X-ray analysis (EDS).
[0019] The average particle diameter of the plurality of metal magnetic particles 10 is, for example, 1 μm or more and 10 μm or less. The average particle diameter of the metal magnetic particles 10 is determined by determining a particle size distribution based on an image of a cross section of the magnetic base 100 photographed at approximately 2000 to 5000 times magnification using a scanning electron microscope, and the average particle diameter of the metal magnetic particles 10 is the particle diameter at 50% of this particle size distribution. By setting the average particle diameter to 10 μm or less, eddy current loss in the metal magnetic particles 10 can be suppressed. By setting the average particle diameter to 1 μm or more, spontaneous combustion caused by natural oxidation of the metal magnetic particles 10 in the atmosphere can be suppressed, improving ease of handling.
[0020] The magnetic substrate 100 may contain two or more kinds of metal magnetic particles 10 with different average particle diameters. For example, it may contain a first metal magnetic particle group and a second metal magnetic particle group with different average particle diameters. The average particle diameter of the second metal magnetic particle group may be 1 / 2 or less of the average particle diameter of the first metal magnetic particle group. When the average particle diameter of the second metal magnetic particle group is smaller than that of the first metal magnetic particle group, the second metal magnetic particles are likely to enter the gaps between adjacent first metal magnetic particles, and the filling rate of the metal magnetic particles is increased. Furthermore, it may contain a third metal magnetic particle group with an average particle diameter smaller than that of the second metal magnetic particle group.
[0021] The magnetic substrate 100 may contain two or more types of metal magnetic particles 10 with different compositions. For example, FeSiCr alloy particles with an increased Si ratio to reduce magnetostriction and improve magnetic permeability, and FeSiCr alloy particles with an increased Fe ratio to improve saturation magnetic flux density may be contained. This allows the magnetic substrate 100 to have the desired magnetic properties.
[0022] The bonding portion 11 is formed using a resinate having at least one element selected from silicon (Si), aluminum (Al), chromium (Cr), magnesium (Mg), titanium (Ti), and zirconium (Zr), as shown in the manufacturing method described later. Therefore, the bonding portion 11 is an amorphous mixture containing an oxide of at least one element selected from Si, Al, Cr, Mg, Ti, and Zr, and carbon (C). The bonding portion 11 may have carbon uniformly dispersed therein, or may have a portion where carbon is concentrated. It is preferable that carbon is distributed throughout the bonding portion 11, and it is preferable that carbon is distributed in 80% or more of the bonding portion 11, and it is more preferable that carbon is distributed in 90% or more of the bonding portion 11. The composition of the bonding portion 11 can be confirmed, for example, by taking a cross-section of the magnetic base 100 at a magnification of about 3000 to 20000 times using a scanning electron microscope, and performing a ZAF method using energy dispersive X-ray analysis (EDS).
[0023] [Manufacturing method] An example of a method for manufacturing a magnetic substrate according to the first embodiment will be described. First, a magnetic paste is prepared by mixing a plurality of metal magnetic particles, a resin composition, and a solvent. Here, the resin composition contains a binder resin and a resinate that is dissolved in the binder resin and contains at least one element selected from the group consisting of Si, Al, Cr, Mg, Ti, and Zr. For example, when the resinate contains Si, it is (R-SiO 1.5 ) n Silsesquioxane having the structure (R: organic functional group), siloxane having a Si-O-Si structure, or a compound having a Si-O skeleton (Si-O structure) other than these, or a mixture of these can be used. In addition, alkoxide having an M-OR structure (M: Si, Al, Cr, Mg, Ti, and / or Zr, R: organic functional group) can be used as the resinate. Resinates dissolved in binder resins do not exist as a solid phase such as filler in the binder resin, but exist as a semi-solid phase or liquid phase including a sol-gel state. Resinates dissolved in binder resins cannot be separated from the binder resin with a general mesh (sieve).
[0024] The solvent may be any material that dissolves the resinate. For example, toluene may be used as the solvent. The binder resin may be any resin that dissolves in the solvent. The binder resin may be a thermosetting resin with excellent insulating properties. For example, the binder resin may be an epoxy resin, a phenol resin, a polyimide resin, a silicone resin, a polystyrene (PS) resin, a high density polyethylene (HDPE) resin, a polyoxymethylene (POM) resin, a polycarbonate (PC) resin, a polyvinyldiene fluoride (PVDF) resin, a polytetrafluoroethylene (PTFE) resin, a polybenzoxazole (PBO) resin, a polyvinyl alcohol (PVA) resin, a polyvinyl butyral (PVB) resin, an acrylic resin, or a mixture thereof. The binder resin and the resinate dissolved in the solvent may each exist alone in the solvent, or may exist in a physically bonded state and / or a chemically bonded state.
[0025] The prepared magnetic paste is applied onto a film such as a polyethylene terephthalate film (PET film) by, for example, a doctor blade method, and then dried in a dryer such as a hot air dryer. The film is then peeled off to form a magnetic layer. Next, a plurality of magnetic layers are laminated and compressed. The compressed magnetic layers are cut into chip units by a dicing machine or a laser processing machine to obtain a chip stack. If necessary, the ends of the chip stack may be subjected to a polishing process such as barrel polishing.
[0026] Next, the chip stack is heat-treated. If the heat treatment is performed in an air atmosphere where a large amount of oxygen is supplied, excessive oxidation tends to proceed in metal magnetic particles with a high iron ratio. For this reason, in the past, when the composition ratio of iron is 92.5 wt% or less, the heat treatment of the chip stack was performed in an air atmosphere, but in the present invention, for example, the heat treatment is performed at 500°C or higher (for example, 600°C to 900°C) and in an atmosphere with an oxygen concentration of 2 ppm to 10,000 ppm for 20 minutes to 120 minutes. By heat treatment at 500°C or higher, the binder resin is thermally decomposed and removed in the process of increasing the temperature to 500°C, but since the resinate has a stronger structure than the binder resin, it is hardly removed in the process of increasing the temperature to 500°C, and the treatment temperature of 500°C or higher gradually progresses to amorphization due to decomposition. By setting the oxygen concentration at this time to 2 ppm to 10,000 ppm, decomposition due to oxidation of carbon constituting the resinate is suppressed. As a result, carbon is taken into the amorphous material. That is, following the decomposition of the binder resin, the metal components (at least one element of Si, Al, Cr, Mg, Ti, and Zr) constituting the resinate are amorphized, and carbon is taken into a part of the amorphous material during this process. As a result, a bonding portion 11, which is an amorphous oxide containing at least one element of Si, Al, Cr, Mg, Ti, and Zr and carbon, is formed on the surface of the metal magnetic particle 10, and a plurality of metal magnetic particles 10 are bonded via the bonding portion 11 to form the magnetic base 100. As in this example, a degreasing heat treatment may be performed during the temperature rise process of the heat treatment, or a heat treatment for a dedicated degreasing process may be performed separately.
[0027] Resinates having at least one element of Si, Al, Cr, Mg, Ti, and Zr can be combined with a binder resin to improve dispersibility, so that the amount of resinate used can be reduced. Therefore, the ratio of the bonding portion 11 in the magnetic substrate 100 can be reduced, and as a result, the ratio of the metal magnetic particles 10, i.e., the packing rate, can be increased. This can suppress the decrease in magnetic permeability. In addition, the good dispersibility improves the ease of manufacturing the magnetic substrate 100. In addition to the bonding portion 11, carbon derived from the resinate may be present in the magnetic substrate 100, and for example, carbon may be present in a triple point surrounded by three or more metal magnetic particles 10.
[0028] According to the first embodiment, a plurality of metal magnetic particles 10 are bonded by a bonding portion 11 which is an amorphous mixture containing an oxide of at least one element selected from Si, Al, Cr, Mg, Ti, and Zr, and carbon. Since the bonding portion 11 which is an amorphous mixture contains carbon, when stress is applied to the magnetic substrate 100 and cracks grow, the growth of the cracks is suppressed by the carbon. This improves the mechanical strength of the magnetic substrate 100. In addition, the bonding portion 11 which bonds the plurality of metal magnetic particles 10 is an amorphous mixture containing an oxide of at least one element selected from Si, Al, Cr, Mg, Ti, and Zr, and the oxides of these elements have high electrical resistivity, so that insulation reliability is ensured.
[0029] When the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is taken as 1, the molar ratio, which is the ratio of the molar amount of carbon contained in the bonding portion 11, is preferably 5 or less. When the ratio of carbon in the bonding portion 11 is high, an electric conduction path is formed by the carbon, which may deteriorate the insulating properties of the magnetic base 100. However, when the total molar amount of Si, Al, Cr, Mg, Ti, and Zr is taken as 1, by setting the ratio of the molar amount of carbon to this to 5 or less, deterioration of the insulating properties of the magnetic base 100 can be suppressed.
[0030] It is preferable that the molar ratio, which is the ratio of the molar amount of carbon contained in the bonding portion 11, is 0.4 or more when the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is 1. If the ratio of carbon in the bonding portion 11 is low, the effect of improving the mechanical strength of the magnetic base 100 is reduced, but if the total molar amount of Si, Al, Cr, Mg, Ti, and Zr is 1, the mechanical strength of the magnetic base 100 can be satisfactorily improved by setting the ratio of the molar amount of carbon to this to 0.4 or more.
[0031] [Second embodiment] FIG. 2 is a cross-sectional view showing a magnetic substrate according to a second embodiment of the present invention. In FIG. 2, a part of the magnetic substrate 200 according to the second embodiment is enlarged and illustrated. Referring to FIG. 2, an oxide film 12, which is an insulating film, is provided to cover at least a part of the surface of the metal magnetic particle 10. The metal magnetic particle 10 can be the same as that of the first embodiment. For example, it is a soft magnetic particle mainly composed of iron, and may be an alloy particle or a pure iron particle. The bonding portion 11 is made of an amorphous mixture containing an oxide of at least one element selected from Si, Al, Cr, Mg, Ti, and Zr and carbon, and is provided in contact with the oxide film 12 on the surface of the multiple metal magnetic particles 10, and the oxide films 12 are bonded to each other via the bonding portion 11, thereby bonding the multiple metal magnetic particles 10. The oxide film 12 may contain an oxide of at least one element selected from Si, Al, Cr, Mg, Ti, and Zr, or may contain an oxide of an element constituting the metal magnetic particle 10. The oxide film 12 contains almost no carbon derived from the resinate, and therefore does not substantially contain carbon unless it is unintentionally contained therein, for example, the proportion of carbon is 1 wt% or less. The oxide film 12 and the bonding portion 11 can be clearly distinguished from each other by the proportion of carbon contained therein. The surface of the oxide film 12 not in contact with the bonding portion 11 may have a film containing carbon derived from the resinate formed separately from the oxide film 12. This film containing carbon derived from the resinate is not involved in the bonding, but has the same composition as the bonding portion 11. The oxide film 12 and the film containing carbon derived from the resinate on the surface of the oxide film 12 can be clearly distinguished from each other by the proportion of carbon contained therein. The oxide film 12 may be amorphous or crystalline, or both may be present. The presence of the oxide film 12 can be recognized as a difference in contrast (brightness) in an image of a cross section of the magnetic substrate 200 photographed at about 5000 times by a scanning electron microscope, for example. The composition of the oxide film 12 can be confirmed by, for example, photographing the cross section of the magnetic base 200 with a scanning electron microscope at a magnification of about 3000 to 20000 times and performing the ZAF method using energy dispersive X-ray analysis. The other configurations are the same as those in the first embodiment, so the description will be omitted.
[0032] [Manufacturing method] An example of a method for manufacturing a magnetic substrate according to the second embodiment will be described. First, the same metal magnetic particles as those in the first embodiment are prepared, and an oxide film is formed on the surface of the metal magnetic particles. The oxide film may be formed on the surface of the metal magnetic particles by a wet method such as a sol-gel method, or may be formed on the surface of the metal magnetic particles by performing a heat treatment on the metal magnetic particles. As an example, a treatment liquid containing TEOS (tetraethoxysilane), ethanol, and water may be mixed into a liquid containing metal magnetic particles, ethanol, and ammonia water to prepare a mixed liquid, and the mixed liquid may be stirred and then filtered to form metal magnetic particles having a silicon oxide film formed on the surface. The metal magnetic particles having a silicon oxide film formed thereon may also be subjected to a heat treatment. The heat treatment may be performed at 400°C to 800°C for 20 minutes to 60 minutes in a reducing atmosphere. Note that an oxide film may be formed on the surface of the metal magnetic particles by a method other than the above, such as a CVD method, a PVD method, or an ALD method. Thereafter, the metal magnetic particles having an oxide film formed on the surface are mixed with a resin composition and a solvent by the same method as that described in the first embodiment to prepare a magnetic paste. The subsequent steps are the same as those in the first embodiment, and therefore the description will be omitted.
[0033] According to the second embodiment, at least a part of the surface of the metal magnetic particle 10 is covered with an oxide film 12 that does not substantially contain carbon. The bonding portion 11, which is made of an amorphous mixture containing an oxide of at least one element selected from Si, Al, Cr, Mg, Ti, and Zr, and carbon, bonds the oxide films 12 together via the bonding portion 11, thereby bonding the multiple metal magnetic particles 10 together. Since the bonding portion 11, which is an amorphous mixture, contains carbon, when stress is applied to the magnetic substrate 200 and cracks grow, the growth of the cracks is suppressed by the carbon. This improves the mechanical strength of the magnetic substrate 200. The bonding portion 11 bonds the oxide films 12 together via the bonding portion 11, thereby bonding the multiple metal magnetic particles 10 together, and the wettability between the bonding portion 11 and the oxide film 12 is good, so that the bonding strength between the multiple metal magnetic particles 10 is improved. This further improves the mechanical strength of the magnetic substrate 200.
[0034] In addition, the bonding portion 11 that bonds the multiple metal magnetic particles 10 is an amorphous mixture containing an oxide of at least one element selected from the group consisting of Si, Al, Cr, Mg, Ti, and Zr, and the oxides of these elements have high electrical resistivity, ensuring insulation reliability. Furthermore, the surfaces of the metal magnetic particles 10 are covered with an oxide film 12, which further improves the insulation of the magnetic base 200. From the viewpoint of improving the insulation of the magnetic base 200, it is preferable that the oxide film 12 contains an oxide of at least one element selected from the group consisting of Si, Al, Cr, Mg, Ti, and Zr. This is because these oxides have high electrical resistivity.
[0035] In the first and second embodiments, the magnetic base is formed by stacking and pressing a plurality of magnetic layers, and then heat-treating the pressed magnetic layers, but it may be formed by other methods. For example, the magnetic base may be formed by filling a cavity of a mold with a magnetic paste prepared by mixing a plurality of metal magnetic particles, a resin composition, and a solvent, and press-molding the molded body, and then heat-treating the molded body.
[0036] [Third embodiment] Fig. 3 is a perspective view showing a coil component according to a third embodiment of the present invention. Fig. 4 is an exploded perspective view showing a coil component according to a third embodiment of the present invention. For convenience of illustration, external electrodes are omitted in Fig. 4. Figs. 3 and 4 show examples of laminated inductors used as passive elements in various circuits as coil components.
[0037] 3 and 4, the coil component 300 has external electrodes 50, 51 provided on the surface of the magnetic base 100. The magnetic base 100 is formed in a generally rectangular parallelepiped shape. The "length" direction, "width" direction, and "thickness" direction of the coil component 300 are illustrated as "L" direction, "W" direction, and "T" direction in Figs. 3 and 4, respectively. The coil component 300 has, for example, a length dimension (dimension in the L axis direction) of 0.2 mm to 6.0 mm, a width dimension (dimension in the W axis direction) of 0.1 mm to 4.5 mm, and a thickness dimension (dimension in the T axis direction) of 0.1 mm to 4.0 mm.
[0038] The magnetic substrate 100 is a laminated body in which the cover layers 20, 26 and the magnetic layers 21-25 are laminated. That is, the magnetic substrate 100 is laminated in the order of the lower cover layer 20, the first magnetic layer 21, the second magnetic layer 22, the third magnetic layer 23, the fourth magnetic layer 24, the fifth magnetic layer 25, and the upper cover layer 26 from bottom to top in FIG. 4. Conductive patterns 31-35 are formed on the magnetic layers 21-25. The conductive patterns 31-35 are embedded in the magnetic layers 21-25 and have upper surfaces that are substantially aligned with the upper surfaces of the magnetic layers 21-25. The cover layers 20, 26 may be formed by laminating a plurality of layers.
[0039] The conductor patterns 31-35 formed on the magnetic layers 21-25 are electrically connected to each other through the vias V1-V4 included in the conductor patterns 32-35. The coil conductor 30 is formed by electrically connecting the conductor patterns 31-35. The coil conductor 30 has a coil axis 36. The coil conductor 30 is formed by winding the conductor patterns 31-35 around the coil axis 36 and is built into the magnetic base 100. The coil axis 36 extends in the T-axis direction. The cover layers 20, 26 and the magnetic layers 21-25 are laminated in the T-axis direction. Therefore, the direction of the coil axis 36 and the lamination direction of the cover layers 20, 26 and the magnetic layers 21-25 are generally the same. One end of the conductor pattern 31 is electrically connected to the external electrode 50, and one end of the conductor pattern 35 is electrically connected to the external electrode 51. The conductive patterns 31 to 35 are formed containing a metal with high conductivity, for example, silver (Ag), palladium (Pd), copper (Cu), aluminum (Al), or an alloy of these.
[0040] [Manufacturing method] An example of a method for manufacturing a coil component according to the third embodiment will be described. First, in the same manner as in the method described in the first embodiment, a magnetic paste prepared by mixing a plurality of metal magnetic particles, a resin composition, and a solvent is applied onto a film, and the magnetic film is formed by drying the magnetic paste. If necessary, a through hole is formed at a predetermined position of the magnetic film, for example, using a laser. A conductor paste such as silver paste or copper paste is applied onto the magnetic film, for example, by screen printing, and the like, and the conductor pattern precursor is formed by drying the conductor paste with a dryer such as a hot air dryer. The above-mentioned magnetic paste is applied onto the magnetic film, for example, by a printing method such as screen printing, and the magnetic film is formed around the conductor pattern by drying the conductor pattern. Then, the film is peeled off. This forms a magnetic layer provided with a conductor pattern.
[0041] The above-mentioned magnetic paste is applied onto the film by, for example, a doctor blade method, and then dried in a dryer to form a magnetic film, after which the film is peeled off, thereby forming the cover layer.
[0042] The magnetic layers and cover layers are laminated in a predetermined order and compressed. The compressed magnetic layers and cover layers are cut into chip units, and then the heat treatment described in the first embodiment is performed. This heat treatment forms bonding portions 11 on the surfaces of the metal magnetic particles 10, and the metal magnetic particles 10 are bonded via the bonding portions 11. As a result, the magnetic layers 21-25 and the cover layers 20, 26 are laminated, and the magnetic base 100 is formed, which incorporates the coil conductor 30 formed by the conductor patterns 31-35. Thereafter, the external electrodes 50, 51 are formed on the surface of the magnetic base 100 by a method used in a thin film process, such as paste printing, plating, or sputtering.
[0043] According to the third embodiment, the coil component 300 includes a magnetic base 100. As described in the first embodiment, the magnetic base 100 includes a plurality of metal magnetic particles 10 bonded together by bonding portions 11 made of an amorphous mixture containing an oxide of at least one element selected from the group consisting of Si, Al, Cr, Mg, Ti, and Zr, and carbon. This improves the mechanical strength of the magnetic base 100 and ensures insulation reliability. Therefore, according to the third embodiment, a coil component 300 is obtained that includes a magnetic base 100 that improves mechanical strength while ensuring insulation reliability.
[0044] [Fourth embodiment] FIG. 5 is a side view showing a coil component according to a fourth embodiment of the present invention. Referring to FIG. 5, the coil component 400 includes a magnetic base 100, a coil winding portion 70, and external electrodes 52 and 53. The shape of the magnetic base 100 may be a drum core, a T core, an I core, or the like, and is not particularly limited. As an example of the shape of the magnetic base 100, a drum core is illustrated. The magnetic base 100 includes a winding core portion 60, a flange portion 61 provided at one end of the winding core portion 60 in the axial direction, and a flange portion 62 provided at the other end of the winding core portion 60. Depending on the shape of the magnetic base 100, one or both of the flange portions 61 and 62 may be absent. The winding core portion 60 has, for example, a substantially rectangular cross-sectional shape, but may be a polygonal shape such as a hexagon or octagon, or may be a circular or elliptical shape. The "length" direction, "width" direction, and "thickness" direction of the coil part 400 are illustrated as "L" direction, "W" direction, and "T" direction, respectively, in Fig. 5. The coil part 400 has, for example, a length dimension (dimension in the L axis direction) of 3.2 mm, a width dimension (dimension in the W axis direction) of 2.5 mm, and a thickness dimension (dimension in the T axis direction) of 2.5 mm.
[0045] The coil winding portion 70 is formed by winding a coated conductor 71 around the winding core portion 60. The external electrode 52 is made of a metal plate and is provided on the flange portion 61. The external electrode 53 is made of a metal plate and is provided on the flange portion 62. As long as the external electrodes 52 and 53 are made of conductive metal, their shapes do not have to be plate-like, and they can be provided at locations other than the flange portions 61 and 62. One end of the coated conductor 71 is electrically connected to the external electrode 52, and the other end is electrically connected to the external electrode 53. The coated conductor 71 has a structure in which the circumferential surface of a core wire made of, for example, copper is covered with an insulating coating made of polyamideimide. The core wire may be made of a metal other than copper, for example, silver, palladium, or a silver-palladium alloy. The insulating coating may be made of an insulating material other than polyamideimide, for example, a resin material such as polyesterimide or polyurethane.
[0046] [Manufacturing method] An example of a method for manufacturing a coil component according to the fourth embodiment will be described. First, in the same manner as in the method described in the first embodiment, a magnetic paste is prepared by mixing a plurality of metal magnetic particles, a resin composition, and a solvent. The magnetic paste is filled into a cavity of a mold and press-molded to form a drum-shaped molded body. If necessary, burrs may be removed from this molded body. The heat treatment described in the first embodiment is performed on this molded body. By this heat treatment, the bonding portion 11 is bonded to the surface of the metal magnetic particle 10, and a magnetic base 100 is formed, which is a drum core in which a plurality of metal magnetic particles 10 are bonded via the bonding portion 11. Then, a coated conductor wire 71 is wound around the magnetic base 100 to form a coil winding portion 70, and the coating of both ends of the coated conductor wire 71 is peeled off. Then, external electrodes 52, 53 connected to the coated conductor wire 71 are formed on the magnetic base 100 by a method used in a thin film process such as paste printing, plating, or sputtering.
[0047] According to the fourth embodiment, the coil component 400 includes a magnetic base 100. As described in the first embodiment, the magnetic base 100 includes a plurality of metal magnetic particles 10 bonded together by bonding portions 11 made of an amorphous mixture containing an oxide of at least one element selected from the group consisting of Si, Al, Cr, Mg, Ti, and Zr, and carbon. This improves the mechanical strength of the magnetic base 100 and ensures insulation reliability. Therefore, according to the fourth embodiment, a coil component 400 is obtained that includes a magnetic base 100 that improves mechanical strength while ensuring insulation reliability.
[0048] In the third and fourth embodiments, the magnetic base 100 according to the first embodiment is used as an example, but the magnetic base 200 according to the second embodiment may also be used.
[0049] [Fifth embodiment] Fig. 6 is a perspective view showing an electronic device according to a fifth embodiment of the present invention. In Fig. 6, solder 82 is hatched for clarity of the drawing. Referring to Fig. 6, electronic device 500 includes a circuit board 80 and coil component 300 of the third embodiment mounted on circuit board 80. Coil component 300 is mounted on circuit board 80 by joining external electrodes 50, 51 to electrodes 81 of circuit board 80 by solder 82. This makes it possible to obtain electronic device 500 including coil component 300 with improved reliability.
[0050] In the fifth embodiment, an example is shown in which the coil component 300 according to the third embodiment is mounted on the circuit board 80, but the coil component 400 according to the fourth embodiment may also be mounted on the circuit board 80. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the embodiments described in these examples.
[0052] [Example 1] The magnetic substrate of Example 1 was produced by the following method. Metal magnetic particles with a composition ratio of silicon: 3.5 wt%, chromium: 2.5 wt%, iron: 94 wt% and an average particle size of 5 μm were used as raw material particles, and the metal magnetic particles, a resin composition, and a solvent were mixed to prepare a magnetic paste. The resin composition was configured to contain polyvinyl butyral (PVB) resin as a binder resin and dimethoxydiphenylsilane as a resinate. Toluene was used as the solvent. The resinate was added so that the weight of the metal magnetic particles was 0.6 wt% in terms of SiO2 weight. This magnetic paste was applied on a PET film and dried at 80°C to form a magnetic film on the PET film. Thereafter, the PET film was peeled off to form a magnetic layer with a thickness of 60 μm to 70 μm.
[0053] Multiple magnetic layers are stacked to achieve a load of 6 ton / cm 2 The laminate was pressed under a hydrostatic pressure of 1000 MPa to produce a laminate with a thickness of about 0.5 mm. Next, a disk sample with an outer diameter of 8 mm, a toroidal sample with an outer diameter of 10 mm and an inner diameter of 5 mm, and a strip-shaped sample with a size of 4 mm x 10 mm were punched out from the laminate, and these samples were heat-treated for 1 hour at 700°C in an atmosphere in which oxygen was added to nitrogen to give an oxygen concentration of 10,000 ppm. As a result, a disk-shaped magnetic substrate, a toroidal-shaped magnetic substrate, and a strip-shaped magnetic substrate were obtained.
[0054] [Example 2] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700° C. in an atmosphere of nitrogen plus oxygen to give an oxygen concentration of 9000 ppm.
[0055] [Example 3] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700° C. in an atmosphere of nitrogen plus oxygen to give an oxygen concentration of 8000 ppm.
[0056] [Example 4] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700° C. in an atmosphere of nitrogen plus oxygen to give an oxygen concentration of 5000 ppm.
[0057] [Example 5] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700° C. in an atmosphere of nitrogen plus oxygen to give an oxygen concentration of 2000 ppm.
[0058] [Example 6] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700° C. in an atmosphere of nitrogen plus oxygen to give an oxygen concentration of 1000 ppm.
[0059] [Example 7] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700° C. in an atmosphere of nitrogen plus oxygen to give an oxygen concentration of 2 ppm.
[0060] [Example 8] Except for the fact that the magnetic paste was prepared using metal magnetic particles with a 20 nm thick silicon oxide film formed on the surface, magnetic substrates of various shapes were produced in the same manner as in Example 1. The silicon oxide film was formed by a sol-gel method.
[0061] [Example 9] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that a magnetic paste was prepared using metal magnetic particles having a 20 nm thick silicon oxide film formed on the surface thereof, and that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere of nitrogen plus oxygen to adjust the oxygen concentration to 9000 ppm.
[0062] [Example 10] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that a magnetic paste was prepared using metal magnetic particles having a 20 nm thick silicon oxide film formed on the surface thereof, and that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere of nitrogen plus oxygen to adjust the oxygen concentration to 8000 ppm.
[0063] [Example 11] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that a magnetic paste was prepared using metal magnetic particles having a 20 nm thick silicon oxide film formed on the surface thereof, and that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere of nitrogen plus oxygen to adjust the oxygen concentration to 5000 ppm.
[0064] [Example 12] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that a magnetic paste was prepared using metal magnetic particles having a 20 nm thick silicon oxide film formed on the surface thereof, and that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere of nitrogen plus oxygen to adjust the oxygen concentration to 2000 ppm.
[0065] [Example 13] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that a magnetic paste was prepared using metal magnetic particles having a 20 nm thick silicon oxide film formed on the surface thereof, and that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere of nitrogen plus oxygen to adjust the oxygen concentration to 1000 ppm.
[0066] [Example 14] Magnetic substrates of each shape were prepared in the same manner as in Example 1, except that a magnetic paste was prepared using metal magnetic particles having a 20 nm thick silicon oxide film formed on the surface thereof, and that the disk sample, toroidal sample, and rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere of nitrogen plus oxygen to adjust the oxygen concentration to 3 ppm.
[0067] [Comparative Example] In the comparative example, a magnetic paste was prepared by mixing metal magnetic particles with a 20 nm thick silicon oxide film formed on the surface, polyvinyl butyral (PVB) resin (binder resin), and toluene (solvent). That is, in the comparative example, a magnetic paste was prepared without using resinate. In addition, a disk sample, a toroidal sample, and a rectangular sample were heat-treated for 1 hour at 700°C in an atmosphere where oxygen was added to nitrogen to give an oxygen concentration of 5000 ppm. Other than these points, magnetic substrates of each shape were prepared in the same manner as in Example 1.
[0068] The magnetic substrates of Examples 1 to 14 and the Comparative Example were evaluated for volume resistivity, flexural strength, relative permeability, and molar ratio. [Volume resistivity] Silver paste was applied to the top and bottom surfaces of the disk-shaped magnetic substrate and then dried to form electrodes. The volume resistivity was calculated from the electrical resistance measured using this electrode and the volume actually measured. [Transverse bending strength] The values were calculated from three-point bending strength tests on rectangular magnetic substrates. [Relative permeability] The relative permeability was calculated by measuring the permeability of the toroidal magnetic substrate using an RF impedance / material analyzer E4991A manufactured by Keysight Technologies. [Mole ratio] The disk-shaped magnetic substrate was cut along the thickness direction to expose the cross section, which was then photographed with a scanning electron microscope (SEM) and the composition of the bonding part that bonds the metal magnetic particles was analyzed by the ZAF method using energy dispersive X-ray analysis (EDS).The molar ratio was calculated as the ratio of the molar amount of carbon (C) contained in the bonding part to the molar amount of silicon (Si) contained in the bonding part.
[0069] The results obtained are shown in Table 1. [Table 1]
[0070] As shown in Table 1, in Examples 1 to 14 prepared using a magnetic paste prepared by including a resinate containing Si, the bending strength was higher than that of the comparative example prepared using a magnetic paste prepared without including a resinate containing Si. This is because, in Examples 1 to 14, a magnetic paste prepared by including a resinate containing Si was used, and the multiple metal magnetic particles 10 were bonded via the bonding portion 11, which is an amorphous mixture containing an oxide of silicon and carbon, so that even when stress was applied to the magnetic base, the growth of cracks was suppressed by the carbon in the bonding portion 11, and the bending strength was increased. In addition, in Examples 1 to 14, a significant decrease in volume resistivity was suppressed. This is because the bonding portion 11 that bonds the multiple metal magnetic particles 10 contains an oxide of Si, which has a high electrical resistivity. Even if it is an oxide of Si, the oxides of Al, Cr, Mg, Ti, and Zr have high electrical resistivity, so when the bonding portion 11 is an amorphous mixture containing an oxide of these elements and carbon, it is considered that the effect of suppressing the decrease in volume resistivity can be obtained. From these findings, it was confirmed that by bonding multiple metal magnetic particles 10 together through bonding portion 11, which is an amorphous mixture containing an oxide of at least one of the elements Si, Al, Cr, Mg, Ti, and Zr and carbon, it is possible to improve mechanical strength while ensuring insulation reliability.
[0071] In addition, as in Examples 7 and 14, when the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is set to 1, when the molar ratio of carbon (C) contained in the bonding portion 11 is greater than 5, the volume resistivity is significantly reduced compared to when the molar ratio of carbon contained in the bonding portion 11 is 5 or less based on the same criteria. This is considered to be because the increase in the proportion of carbon in the bonding portion 11 makes it easier to form a path of electrical conduction by carbon. From this, it was confirmed that insulation reliability can be improved by setting the molar ratio, which is the ratio of the molar amount of carbon (C) contained in the bonding portion 11 to 5 or less when the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is set to 1. It was confirmed that the molar ratio is preferably 4.8 or less, more preferably 4.4 or less, and even more preferably 3.0 or less from the viewpoint of improving insulation reliability.
[0072] In addition, as in Examples 1 to 14, when the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is 1, the result that the bending strength is high was obtained when the molar ratio of carbon (C) contained in the bonding portion 11 to the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is 0.4 or more. Therefore, it was confirmed that the mechanical strength can be improved by setting the molar ratio, which is the ratio of the molar amount of carbon (C) contained in the bonding portion 11 to the total molar amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 to 1, to 0.4 or more. From the viewpoint of improving the mechanical strength, it was confirmed that the molar ratio is preferably 0.42 or more, more preferably 0.51 or more, and even more preferably 1.3 or more.
[0073] The molar ratios in Table 1 are the ratio of the molar amount of carbon (C) to the molar amount of silicon (Si), but since the molar amounts are compared, it is considered that the same effect can be obtained when the ratio of the molar amount of carbon (C) to the total molar amount of Si, Al, Cr, Mg, Ti, and Zr satisfies the above requirements. Also, since Table 1 shows the results when the bonding portion 11 is an oxide containing silicon (Si) and carbon (C), it can be said that it is preferable for the amorphous mixture of the bonding portion 11 to contain silicon oxide as a main component. The term "containing silicon oxide as a main component" refers to the case where the ratio of Si to the total amount of Si, Al, Cr, Mg, Ti, and Zr contained in the bonding portion 11 is 50 wt% or more, preferably 70 wt% or more, more preferably 80 wt% or more, and even more preferably 90 wt% or more.
[0074] In addition, in Examples 8 to 14 in which the oxide film 12 is formed on the surface of the metal magnetic particle 10 and the oxide films 12 of the metal magnetic particles 10 are bonded to each other via the bonding portion 11, the flexural strength and volume resistivity are higher than those in Examples 1 to 7 in which the oxide film 12 is not formed on the surface of the metal magnetic particle 10. The oxide films 12 of the metal magnetic particles 10 are bonded to each other via the bonding portion 11, and the wettability of the bonding portion 11 and the oxide film 12 is improved, and as a result, the bonding strength between the metal magnetic particles 10 via the bonding portion 11 is improved, which is thought to have improved the flexural strength. It is thought that the volume resistivity is increased because the surface of the metal magnetic particle 10 is covered with the oxide film 12. From this, it was confirmed that by covering at least a portion of the surface of the metal magnetic particle 10 with an oxide film 12 that is substantially free of carbon, and by bonding the oxide films 12 together via the bonding portions 11, and thereby bonding multiple metal magnetic particles 10, it is possible to improve mechanical strength and insulation reliability.
[0075] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to such specific embodiment, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]
[0076] 10 Metal magnetic particles 11 Joint 12 Oxide film 20, 26 Cover layer 21~25 Magnetic layer 30 Coil conductor 31~35 Conductor pattern 50~53 External electrode 60 Winding core 61, 62 flange 70 Coil winding section 71 Covered conductor wire 80 Circuit Board 81 Electrode 82 Solder 100, 200 magnetic substrate 300, 400 Coil parts 500 Electronic equipment
Claims
1. A magnetic substrate including a plurality of magnetic layers each including a plurality of metal magnetic particles and a bonding portion bonding the plurality of metal magnetic particles; a coil conductor formed by a conductor pattern provided on the plurality of magnetic layers and embedded in the magnetic base; an external electrode provided on a surface of the magnetic base and connected to the coil conductor; the bonding portion is an amorphous mixture containing an oxide of silicon as a main component and carbon, A laminated inductor, wherein a molar ratio, which is a ratio of a molar amount of carbon contained in the bonding portion to a molar amount of silicon contained in the bonding portion taken as 1, is 0.4 or more.
2. 2. The laminated inductor according to claim 1, wherein a molar ratio, which is a ratio of a molar amount of carbon contained in said bond portion to a molar amount of silicon contained in said bond portion taken as 1, is 5 or less.
3. A magnetic substrate including a plurality of magnetic layers each including a plurality of metal magnetic particles and a bonding portion that bonds the plurality of metal magnetic particles; a coil conductor formed by a conductor pattern provided on the plurality of magnetic layers and embedded in the magnetic base; an external electrode provided on a surface of the magnetic base and connected to the coil conductor; the bonding portion is an amorphous mixture containing an oxide of silicon as a main component and carbon, and also contains an oxide of at least one element of aluminum, chromium, magnesium, titanium, and zirconium; A laminated inductor, wherein a molar ratio, which is the ratio of the molar amount of carbon contained in the bonding portion to the total molar amount of silicon, aluminum, chromium, magnesium, titanium, and zirconium contained in the bonding portion taken as 1, is 0.4 or more.
4. 4. The laminated inductor according to claim 3, wherein a molar ratio, which is a ratio of a molar amount of carbon contained in the bonding portion to a total molar amount of silicon, aluminum, chromium, magnesium, titanium, and zirconium contained in the bonding portion, is 5 or less.
5. an oxide film that covers at least a portion of the surfaces of the metal magnetic particles and is substantially free of carbon; The laminated inductor according to claim 1 , wherein the bonding portion bonds the oxide films together via the bonding portion, thereby bonding the plurality of metal magnetic particles together.
6. The laminated inductor according to claim 1 , wherein the plurality of metallic magnetic particles are composed mainly of iron.
7. 4. The laminated inductor according to claim 1, wherein said magnetic substrate has a region where carbon is present other than said bonded portions.
8. 8. The laminated inductor according to claim 7, wherein the region other than the bonding portion where carbon is present is a triple point portion surrounded by three or more of the plurality of metal magnetic particles.
9. The laminated inductor according to claim 1 , wherein the conductor pattern comprises silver, palladium, copper, or aluminum.
10. Providing a plurality of metallic magnetic particles; A step of preparing a magnetic paste by mixing the plurality of metal magnetic particles, a resin composition containing a binder resin and a resinate containing silicon, and a solvent; forming a plurality of magnetic layers using the magnetic paste; forming a conductor pattern on the plurality of magnetic layers; a step of laminating the plurality of magnetic layers on which the conductive pattern is formed, and then heat-treating the plurality of magnetic layers to form bonding parts on the surfaces of the plurality of metal magnetic particles, the bonding parts being an amorphous mixture containing, as a main component, an oxide of silicon contained in the resinate and containing carbon, and forming a magnetic substrate in which the plurality of metal magnetic particles are bonded via the bonding parts and which incorporates a coil conductor formed by the conductive pattern; forming an external electrode connected to the coil conductor on a surface of the magnetic base, A molar ratio, which is a ratio of a molar amount of carbon contained in the bonding portion to a molar amount of silicon contained in the bonding portion taken as 1, is 0.4 or more.
11. 11. The method for manufacturing a laminated inductor according to claim 10, wherein in the step of forming the magnetic base, the magnetic layers are heat-treated to thermally decompose the binder resin before the resinate, and then the silicon component of the resinate is made amorphous while incorporating carbon contained in the resinate, thereby forming the bonding portion on the surface of the metal magnetic particles.
12. In the step of preparing a plurality of metal magnetic particles, the plurality of metal magnetic particles are provided with an oxide film on their surfaces; 12. The method for manufacturing a laminated inductor according to claim 10, wherein in the step of forming the magnetic base, the magnetic base is formed in which the oxide films of the plurality of metal magnetic particles are bonded together via the bonding portions.
Citation Information
Patent Citations
Powder of soft magnetic metal, green compact thereof, and method for manufacturing powder of soft magnetic metal
JP2008195986A
Powder magnetic core and manufacturing method thereof
JP2009088362A
Soft magnetic material and manufacturing method thereof, dust core containing the soft magnetic material
JP2009212143A
Silica-based insulated coated dust core, method for manufacturing the same, and electromagnetic circuit part
JP2017188678A
Magnetic material and electronic component
JP2018011043A